2005
DOI: 10.1063/1.1955127
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of a capsule in simple shear flow: Effect of membrane prestress

Abstract: We investigate the effect of an initial isotropic prestress on the mechanics of a spherical capsule freely suspended in a simple shear flow. The capsule consists of a drop of liquid enclosed by a very thin hyperelastic membrane. A sufficient prestress may prevent the buckling instability that arises at low shear rates when the membrane bending resistance is neglected. A small perturbation analysis of the capsule deformation is first obtained for small prestress and weak viscous stresses. When the viscous shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 21 publications
3
68
0
2
Order By: Relevance
“…Large deformation of red blood cell ghosts was simulated by (Eggleton and Popel, 1998) using the Immersed Boundary Method (IBM) that reproduced the tank treading behavior observed experimentally in shear flow (Fischer, et al, 1978). (Lac and Barthes-Biesel, 2005) computed elastic capsule deformation in simple shear flow and hyperbolic flow using the Boundary Element method, and showed that steady shapes were obtained only within stable capillary number ranges. Outside of the stable capillary number ranges, the capsules either go through continuous elongation or a membrane buckling instability develops.…”
Section: Introductionmentioning
confidence: 99%
“…Large deformation of red blood cell ghosts was simulated by (Eggleton and Popel, 1998) using the Immersed Boundary Method (IBM) that reproduced the tank treading behavior observed experimentally in shear flow (Fischer, et al, 1978). (Lac and Barthes-Biesel, 2005) computed elastic capsule deformation in simple shear flow and hyperbolic flow using the Boundary Element method, and showed that steady shapes were obtained only within stable capillary number ranges. Outside of the stable capillary number ranges, the capsules either go through continuous elongation or a membrane buckling instability develops.…”
Section: Introductionmentioning
confidence: 99%
“…In all that follows, the capillary number ε will be based on the inflated capsule radius a, rather than the unstressed capsule radius a 0 , because it is a that is usually measured. As shown by Lac & Barthès-Biesel (27) , when such a pre-inflated capsule is suspended in a simple shear flow, the pre-stress can compensates the negative tensions that appear at low shear rates and membrane buckling can thus be avoided (figure 2.4). Altogether, the global effect of pre-stress is to decrease the capsule deformation for a given shear rate and to increase significantly the elastic tension in the membrane at a given deformation level.…”
Section: Deformation Of a Pre-stressed Capsule In A Simple Shear Flowmentioning
confidence: 98%
“…Correspondingly, a capsule with a 10% pre-inflation and a SK membrane necessitate quite large values of capillary number ε to reach a 60% deformation. Lac & Barthès-Biesel (27) also show that for a preinflated…”
Section: Deformation Of a Pre-stressed Capsule In A Simple Shear Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Different parameters can influence the deformation and orientation dynamics of microcapsules, e.g. capsule shape [1], bending stiffness [2,3,4,5], viscosity ratio of the inner and outer phase [6], membrane constitutive laws [7] and membrane pre-stress [8]. The surrounding membranes sometimes showed shear induced wrinkling instabilities [9].…”
Section: Introductionmentioning
confidence: 99%